Crop plants as models for understanding plant adaptation and diversification - Olsen, Kenneth M.; Wendel, Jonathan F. (Frontiers in Plant Science, 2013)
Since the time of Darwin, biologists have understood the promise of crop plants and their wild relatives for providing insight into the mechanisms of phenotypic evolution. The intense selection imposed by our ancestors during plant domestication and subsequent crop improvement has generated remarkable transformations of plant phenotypes. Unlike evolution in natural settings, descendent and antecedent conditions for crop plants are often both extant, providing opportunities for direct comparisons through crossing and other experimental approaches. Moreover, since domestication has repeatedly generated a suite of “domestication syndrome” traits that are shared among crops, opportunities exist for gaining insight into the genetic and developmental mechanisms that underlie parallel adaptive evolution. Advances in our understanding of the genetic architecture of domestication-related traits have emerged from combining powerful molecular technologies with advanced experimental designs, including nested association mapping, genome-wide association studies, population genetic screens for signatures of selection, and candidate gene approaches. These studies may be combined with high-throughput evaluations of the various “omics” involved in trait transformation, revealing a diversity of underlying causative mutations affecting phenotypes and their downstream propagation through biological networks. We summarize the state of our knowledge of the mutational spectrum that generates phenotypic novelty in domesticated plant species, and our current understanding of how domestication can reshape gene expression networks and emergent phenotypes. An exploration of traits that have been subject to similar selective pressures across crops (e.g., flowering time) suggests that a diversity of targeted genes and causative mutational changes can underlie parallel adaptation in the context of crop evolution.